Amino Acid Oxidation of Candida antarctica Lipase B Studied by Molecular Dynamics Simulations and Site-Directed Mutagenesis - Irani, Mehdi; Törnvall, Ulrika; Genheden, Samuel; Wittrup Larsen, Marianne; Hatti-Kaul, Rajni; Ryde, Ulf (Biochemistry, 2013)
Molecular dynamics simulations have been performed on lipase B from Candida antarctica (CalB) in its native form and with one or two oxidized residues, either methionine oxidized to methionine sulfoxide, tryptophan oxidized to 5-hydroxytryptophan, or cystine oxidized to a pair of cysteic acid residues. We have analyzed how these oxidations affect the general structure of the protein as well as the local structure around the oxidized amino acid and the active site. The results indicate that the methionine and tryptophan oxidations led to rather restricted changes in the structure, whereas the oxidation of cystines, which also caused cleavage of the cystine S-S linkage, gave rise to larger changes in the protein structure. Only two oxidized residues caused significant changes in the structure of the active site, viz., those of the Cys-22/64 and Cys-216/258 pairs. Site-directed mutagenesis studies were also performed. Two variants showed a behavior similar to that of native CalB,(M83I and M129L), whereas W155Q and M72S had severely decreased specific activity. M83I had a slightly higher thermostability than native CalB. No significant increase in stability toward hydrogen peroxide was observed. The same mutants were also studied by molecular dynamics. Even though no significant increase in stability toward hydrogen peroxide was observed, the results from simulations and site-directed mutagenesis give some clues about the direction of further work on stabilization.